A Justiça Federal na Era Vargas - Schwaitzer, Lenora de Beaurepaire da Silva (2012)
This study is a retrospective analysis of the main discussions during the early years of the Vargas Era on the Judiciary organization in the quest to find the motivations that have caused the extinction of the First Instance Federal Courts through the Constitution granted on November 10th, 1937. From the 1930 Revolution there will be presented the main trends of the Justice System discussed during the Itamaraty (Ministry of Foreign Relations) subcommittee sessions created to elaborate a Constitution draft at the request of the leader of the Provisional Government and also at the 1934 National Constituent Assembly sessions. Starting from primary sources such as laws, meeting minutes, letters and articles published in journals of the time, the research will point out the importance of discussions on the Judiciary occurred at the time to the conception of the National State which was in full development. In order to understand the context in which the above-mentioned primary sources are located, the focus was on analyzing the academic papers developed in the 1980’s, mainly by the Center for Research and Documentation on the Contemporary History of Brazil (CPDOC) which help the understanding of a troubled period of the recent national past. The work supports that, rather than administrative or legal doctrinal issues, it was the body of ideas that involved the conception of the so-called New State that created the endorsing ideological and political conditions, not consolidated at the previous period of time, and that resulted in the non-inclusion of the First Instance Federal Court among the Judiciary organs in the 1937 Constitution.